The Influence Of Workload, Work Environment, And Compensation On Employee Performance At Pt Bintang Selatan Agung - Lisa Diyahanip; Luis Marnisah; Tien Yustini (Syntax Literate, 2022)
The purpose of this study was to determine the effect of workload, work environment, and compensation on employee performance at pt bintang selatan agung, both partially and simultaneously. The research method uses a descriptive quantitative approach using the spss 25 program. The population of this study is 143 employees of pt. Bintang selatan agung with a sample taken from the total population and the level of precision (error) of 5% from the slovin formula, namely 105 employees at pt. Great southern star. Testing the data using the t test, the workload variable on employee performance shows that the tcount value is 4.346 > ttable 1.984, the work environment variable on employee performance has a tcount value of 7.122 > ttable 1. 984, and the compensation variable on employee performance has a tcount of 3.520 > ttable 1.984. Testing the data using the f test also found that workload, work environment and compensation have a value of fcount 59.244 > ftable 2.69. The results of the study can be concluded that workload, work environment and compensation have a positive and significant effect on the performance of employees of pt. South star agug either partially or simultaneously.